NADH and NADPH peroxidases as antioxidant defense mechanisms in intestinal sulfate-reducing bacteria - Kushkevych, Ivan; Dordević, Dani; Alberfkani, Mohammad I; Gajdács, Márió; Ostorházi, Eszter; Vítězová, Monika; Rittmann, Simon K-M R (Scientific reports, 2023)
Animal and human feces typically include intestinal sulfate-reducing bacteria (SRB). Hydrogen sulfide and acetate are the end products of their dissimilatory sulfate reduction and may create a synergistic effect. Here, we report NADH and NADPH peroxidase activities from intestinal SRB Desulfomicrobium orale and Desulfovibrio piger. We sought to compare enzymatic activities under the influence of various temperature and pH regimes, as well as to carry out kinetic analyses of enzymatic reaction rates, maximum amounts of the reaction product, reaction times, maximum rates of the enzyme reactions, and Michaelis constants in cell-free extracts of intestinal SRB, D. piger Vib-7, and D. orale Rod-9, collected from exponential and stationary growth phases. The optimal temperature (35 °C) and pH (7.0) for both enzyme's activity were determined. The difference in trends of Michaelis constants (Km) during exponential and stationary phases are noticeable between D. piger Vib-7 and D. orale Rod-9; D. orale Rod-9 showed much higher Km (the exception is NADH peroxidase of D. piger Vib-7: 1.42 ± 0.11 mM) during the both monitored phases. Studies of the NADH and NADPH peroxidases-as putative antioxidant defense systems of intestinal SRB and detailed data on the kinetic properties of this enzyme, as expressed by the decomposition of hydrogen peroxide-could be important for clarifying evolutionary mechanisms of antioxidant defense systems, their etiological role in the process of dissimilatory sulfate reduction, and their possible role in the development of bowel diseases.
Keywords: Animals; Sulfates; Desulfovibrio; NADP; obranné mechanismy; sírany; lidé; Antioxidants; peroxidasy; zvířata; Defense Mechanisms; Peroxidases; NAD; Cell Extracts; antioxidancia; buněčné extrakty; Humans